Dysphagia lusoria caused by an aberrant right subclavian artery - Hassan, Radhiana; Md Ralib @ Md Raghib, Ahmad Razali; Wan Leman, Wan Ishlah (2009)
Dysphagia of vascular origin is termed dysphagia lusoria and it is relatively uncommon. Amongst the vascular causes, aberrant right subclavian artery is the most common. This case illustrates the usefulness of imaging in the investigation of dysphagic patient for an accurate diagnosis and appropriate management of the condition.